An engineering method of aerodynamic heating prediction for hypersonic blunt body vehicles - Jimin Chen; Guoyi He (Advances in Mechanical Engineering)
This paper develops a rapid engineering method for predicting aerodynamic heating of hypersonic blunt body vehicles and implements a complete computational program in C++. This engineering method is used to reduce the time required to predict the aerodynamic heating for vehicles. It utilizes the Kemp-Riddell formula to calculate stagnation point heat flux, while the downstream region heat flux is determined using the reference enthalpy method. Additionally, a simplified streamline tracing approach is proposed to calculate inviscid surface streamlines, achieving a 90% improvement in computational efficiency. A mean filtering method is also introduced to triangular surface meshes to effectively improve the smoothness of the local Reynolds number on low-density surface meshes. The engineering method is validated against experimental data from a spherically blunted cone and an Orbiter Vehicle model, showing good agreement in wall heat flux predictions for small angles of attack, with a relative error of less than 15% in the stagnation and non-expanded downstream regions. A comparison between the perfect gas model and the chemical equilibrium gas model indicates that, while their results are generally similar, the perfect gas model reduces computational time by 70% in related calculation processes, making it suitable for most conditions.